Motor development: analysis of Brazilian studies on fundamental motor skills - Hélder Ferreira Isayama; Jorge Sergio Perez Gallardo (Revista da Educação Física)
Along the years, the motor development field of study has drawn the attention of a great number of researchers such as Clark (1994), Gallahue (1989) and Haywood (1986). The central focus of their studies was to understand how human beings develop increasingly complex and coordenate motor skills. Since the establishment of this field of studies, it has been influenced by different perspectives, two of which are fundamental to the understanding of the development process: the maturational perspective and the dynamic systems perspective. Very little has been investigated, in Brazil, on fundamental motor skills development. Thus, the objective of this paper is to discuss the courses of these researches. Nowadays, it is perceptible that, despite the great influence of the maturational perspective those studies have suffered, there exists an agreement among researchers on the importance of the effective participation of the physical and social environment in motor development of human beings.